Linguistic Didacticism in the Noctes Atticae by Aulus Gellius - Wolanin, Hubert (Symbolae Philologorum Posnaniensium Graecae et Latinae, 2017)
The aim of this paper is to examine the didactic value of the Attic Nights from the linguistic point of view, and precisely, from the point of view of Gellius’ teachings on the meanings of words. In this context it has been stated that the author makes his readers aware of new meanings gained by certain words when used in contemporary colloquial idiom, describes and interprets the mechanism which had generated those meanings, evaluates the results of the process of semantic change, and, finally, comments on the way some grammarians assess the usage of certain words in ancient literary texts. In effect, the paper concentrates on the passages where A. Gellius, referring to ancient (archaic and classical) literature, describes the semantic differences occurring in various words, depending on their usage, whether in literary or colloquial language, defines the linguistic mechanism giving rise to colloquial variants of different linguistic items, and presents in a critical light the influence of colloquial language on the way in which interpretation is made of particular words as they occur in literary texts.